Social Rehabilitation and Its Effectiveness in Narcotics Institutions for Integrated Citizens in Indonesia - Endah Ratnawaty Chotim (Budapest International Research and Critics University, 2022)
To create a better society, it is necessary to have rehabilitation that can be carried out for former narcotics users in Indonesia. This study aims to see how social rehabilitation provides a second chance for prisoners in prison in narcotics prisons. Through this research, the effectiveness of rehabilitation will be investigated. This research will use a qualitative approach with data sources obtained from previous research and studies that are still relevant. The study results found that social rehabilitation has a high enough effectiveness for narcotics addicts to get out of the grip of narcotics. This effectiveness is caused by prisons that use the Therapeutic Community method. In this method, there are four stages in the form of detox, induction, primary to the last stage in the form of re-entry.